War comes to the Big Bend: a western story (Five Star, Skyhorse, 2014)
First serialized in 1919, the novel takes place during WWI and tellls the story of Kurt Dorn, a wheat farmer in the state of Washington whose father is German and his mother American. Though he has a successful farm, there are groups that would like to prevent wheat from being harvested at all, including a group of Bolsheviks, the Industrial Workers of the World, which is led by a German spy financed not only by Germany but also secretly by a German wheat magnate.